What Are the Most Important Factors Influencing Springtail Tetrodontophora bielanensis? - Mladenović, Strahinja; Materna, Jan; Brestovanská, Tereza; Horák, Jakub (Insects, 2021)
The springtail, Tetrodontophora bielanensis, dwells in the litter and upper soil layers. This arthropod mainly inhabits humid litter and soil and prefers a cold climate. We determined the main factors influencing this springtail in forests at the landscape level in Krkonoše and site level in Orlické hory in the Czech Republic. We used passive trunk-tree traps. These traps are highly effective for sampling flightless fauna. We used 128 traps in Krkonoše and 17 traps in Orlické hory. The springtail was significantly positively influenced by the presence of Norway spruce (Picea abies) at the landscape level. Springtails' abundance was, furthermore, influenced by the spatial distribution of the sampling sites. The negative influence of bark coverage and the presence of fungi, and positive influence of an increasing dimension of trees were significant at the site level. We argue for a more diversified management of mountainous forests with respect to forest history. This appears to be also important for mountainous forests in protected areas.
Keywords: European beech; Norway spruce; spatial autocorrelation; dead wood; saproxylic microhabitats